Extended half‐life rFIX in major surgery—How to improve clinical practice: An intraindividual comparison. Issue 3 (12th February 2020) - Valeri, Federica; Agnelli Giacchello, Jacopo; Dainese, Cristina; Valpreda, Alessandra; Montaruli, Barbara; Dosio, Enrico; Boccadoro, Mario; Borchiellini, Alessandra
Abstract: Practical, safe, and effective hemostatic approach to orthopedic surgery using Extended Half‐Life factor IX in hemophilia B. By intraindividual comparison, we found a lower FIX consumption, number of infusions, and cost compared to plasma‐derived FIX. Abstract : Practical, safe, and effective hemostatic approach to orthopedic surgery using Extended Half‐Life factor IX in hemophilia B. By intraindividual comparison, we found a lower FIX consumption, number of infusions, and cost compared to plasma‐derived FIX.